Developmentally supportive care in neonatology: Correlational study of the knowledge and declared practices of professionals. (December 2022) - Faez, Naima; Hmami, Fouzia; Kojmane, Widade; Atmani, Samir
Abstract: Background: In the Neonatal Intensive Care Unit, preterm neonates present a neurodevelopmental risk expressed by physiological and behavioral signs that are difficult to interpret. This neonatal stress is generated by clinical practices, which can affect the quality of care. This is why neonatology teams must participate in the development of multidisciplinary actions for early intervention, hence the integration of Developmental Supportive Care. Methods: This is the first quantitative descriptive correlational study, with a comprehensive sample of 56 medical, nursing, and caregiver professionals practicing in the neonatology and intensive care unit at Hassan II University Hospital in Fez, Morocco, between May and October 2019. The data collection tool chosen was a self-administered questionnaire based on the Likert scale" composed of five statements. Results: Developmental care is more or less integrated, in an anarchic way, into clinical practice. Remarkable deficiencies were identified with a statistically significant correlation between knowledge and practice. Participants with declared knowledge scored an average of 28.667 of Developmental Care practices. While those, having reached the highest average 31.154, are located at the average level of knowledge. Certainly, 22.241 is the lowest level on both dimensions. The professionals most involved in the practices have only an average level of knowledge in this area. Conclusions: In the absence of a Developmental Care program in the national health system, implementation of this approach requires considerable effort. It would be interesting to repeat an evaluation of knowledge and practices after integrating new programs and specific protocols for individualized care in neonatology. Highlights: Developmental Care contributes to improving the quality of neonatal life. Professionals must develop multidisciplinary approaches to clinical practice. This research identified a low level of knowledge and practice in Developmental Care. Significant correlations were detected between clinical practice and knowledge. The implementation of Developmental Care seems to be a priority.